Factors in the Sharing of Tacit Knowledge among Volunteer Firefighters - Oliveira, Márcio (2021)
The studies in the area of knowledge management, directed to non-profit organizations are scarce, as opposed to what happens in the private and public sector. The growing importance of the third sector and its institutions, in establishing a more just and balanced society, combating asymmetries and placing itself on the side of the neediest, justifies the attention of the academic community, in order to establish and adopt best practices to carry out their missions. The choice of a case study of organizations such as the Portuguese fire brigades, unique in their action and identity, accompanies the need increasingly recognized by Portuguese society to enable these organizations to perform best in the face of tragic events in recent years in Portugal, particularly in the case of large fires. This study focuses on analysing the sharing of tacit knowledge in non-profit organisations (NPOs) through the case of Portuguese volunteer firefighters (Vfs). A literature review on tacit knowledge sharing allowed the identification of indicators to share this knowledge. A quantitative methodology was followed, with data collection through questionnaires and the treatment of which was able to determine the indicators that influence each factor. We correspondingly applied exploratory factorial analysis to study the indicators for the tacit sharing of knowledge. This returned three factors as leading to the sharing of tacit knowledge within the scope of these organisations: organisational culture, individual characteristics and organisational structure.